2021
DOI: 10.3892/etm.2021.9680
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PIG11 correlates with poor prognosis in gastric cancer

Abstract: P53-induced gene 11 (PIG11) is an early transcription-related target of p53 that is involved in cell apoptosis and tumor development. However, its biological function in gastric cancer (GC) tissues and relationship with the prognosis of patients with GC have remained elusive. In the present retrospective study, 60 fresh and 790 paraffin-embedded samples of GC were obtained from the Affiliated Hospital of Nantong University (Nantong, China) with complete clinical data from all patients. Reverse transcription-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In adult stem cells, reduced P53 aids in reprogramming ( Marion et al, 2009 ; Maeso-Alonso et al, 2021 ), whereas P73 aids in controlling cell cycle progression and plays additional rolls in cell–adhesion and cell–ECM interactions ( Maeso-Alonso et al, 2021 ). A positive correlation between P53 , P73 , and Ki67 transcript levels was noted in all cell types, with higher levels in IVD over FAT cells, whereas P53-induced protein 11 transcripts ( TP53I11 , Pig11 ) ( Gu et al, 2021 ) showed a negative correlation and were downregulated in IVD over FAT cells. Perp encoding an effector in the TP53-dependent apoptotic pathway was also downregulated in NP over FAT cells in 2D culture.…”
Section: Discussionmentioning
confidence: 88%
“…In adult stem cells, reduced P53 aids in reprogramming ( Marion et al, 2009 ; Maeso-Alonso et al, 2021 ), whereas P73 aids in controlling cell cycle progression and plays additional rolls in cell–adhesion and cell–ECM interactions ( Maeso-Alonso et al, 2021 ). A positive correlation between P53 , P73 , and Ki67 transcript levels was noted in all cell types, with higher levels in IVD over FAT cells, whereas P53-induced protein 11 transcripts ( TP53I11 , Pig11 ) ( Gu et al, 2021 ) showed a negative correlation and were downregulated in IVD over FAT cells. Perp encoding an effector in the TP53-dependent apoptotic pathway was also downregulated in NP over FAT cells in 2D culture.…”
Section: Discussionmentioning
confidence: 88%
“…Immunohistochemical staining. We used immunohistochemical staining analysis according to the [29]. For antigen retrieval, the TMA slides are dewaxed, rehydrated and boiled in a pressure pot with sodium citrate buffer (pH 6.0).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments have indicated the suppression of epithelial-mesenchymal transition and metastasis in breast cancer cells [ 12 ] and enhanced apoptosis in liver cancer cells [ 10 , 11 ]. Conversely, other studies have suggested that TP53I11 may play a role in promoting the development and progression of certain cancers [ 9 , 14 ]. In a recent bioinformatics study, it was found that breast cancer has a considerably elevated expression of TP53I11, and patients with low levels of expression tend to have a better survival rate [ 14 ].…”
Section: Introductionmentioning
confidence: 95%
“…TP53I11 was one of the genes identified in the study. Studies have shown that TP53I11 is primarily expressed in the mammary gland, liver, and gastrointestinal tract, as well as in the corresponding cancer tissues [ 9 ]. Research has also linked TP53I11 to the development and progression of various types of tumors, including non-small cell lung, breast, liver, and gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation